Análise comparativa de custo e produtividade dos sistemas construtivos: alvenaria de solo-cimento, alvenaria com blocos cerâmicos e alvenaria estrutural com blocos de concreto na construção de uma residência popular - Penteado, Priscilla Troib (2011)
This study presents, from the viewpoint of building systems in Civil Engineering, an analysis of pros and disadvantages of the constructive process with soil-cement compared to the conventional construction process and the concrete block masonry. This comparative examination was made considering costs and runtime of the stages of structure and sealing and internal and external coatings of a popular two-bedroom residence and with thirty-three square meters, set to the three building systems. The proceedings have been studied and was also conducted a review of budget worksheets and producing of these systems. The benefit of the use of soil-cement compared to conventional masonry with concrete-block takes place in relation to time of completion, costs, waste of materials, environmental pollution, among others, especially when this applies to several units building, as in federal housing programs. It was found that costs of a home unit on the system soil-cement are shorter than in the conventional system and masonry, as well as productivity is the greatest among all three systems.